A Phase II Study of Celecoxib With Irinotecan, 5-Fluorouracil, and Leucovorin in Patients With Previously Untreated Advanced or Metastatic Colorectal Cancer. (December 2018) - Chen, Emerson Y.; Blanke, Charles D.; Haller, Daniel G.; Benson, Al B.; Dragovich, Tomislav; Lenz, Heinz-Josef; Robles, Carlos; Li, Hong; Mori, Motomi; Mattek, Nora; Sanborn, Rachel E.; Lopez, Charles D.
Abstract : Objective: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. Cyclooxygenase-2 (COX-2) overexpression is associated with increased tumor invasiveness and proliferation in CRC, and COX-2 inhibition has demonstrated chemopreventive activity. This study investigated the addition of celecoxib, a selective COX-2 inhibitor, to the irinotecan, 5-fluorouracil, and leucovorin (IFL) regimen for patients with previously untreated metastatic CRC. Patients and Methods: Forty-seven patients enrolled in this single-arm phase II study received celecoxib at 400 mg orally twice daily in combination with weekly irinotecan (125 mg/m 2 ), 5-fluorouracil (500 mg/m 2 ), and leucovorin (20 mg/m 2 ) for 4 weeks every 6 weeks. The primary endpoint was response rate (RR) as measured by Response Evaluation Criteria in Solid Tumors. The protocol was amended midway to additionally exclude patients with Eastern Cooperative Oncology Group performance status 2 and require all patients with specific cardiovascular risk factors to take daily aspirin (81 mg). Results: The objective RR was 31.9% (95% confidence interval [CI], 19%-47%). Median progression-free survival was 8.7 months (95% CI, 5.8-10.6), and the median overall survival was 19.7 months (95% CI, 15.4-22.8). All cardiac events were observed before protocol modification. The median overall survival before and after protocol modification was 11.4 versus 24.2 months, respectively ( P <0.0001); tumor RR and progression-free survival were not statistically different before or after protocol modification. The trial was halted after an interim analysis demonstrated that the primary endpoint would not be met. Conclusions: Celecoxib plus IFL chemotherapy for patients with metastatic CRC is tolerable, but does not appear to increase the efficacy of IFL.